Effect of different levels of green tea waste supplementation on in vitro digestibility and ruminal fermentation - Lunsin, Ratchataporn; Wanapat, Metha; Sokantat, Damrongchai; Boonthawee, Kittawat (Agriculture and Natural Resources, 2022)
Importance of the work: The high nutritive value and multiple functional components of green tea waste (GTW) could be used as alternative feedstuff for ruminants. Objectives: To investigate the effects of different levels of GTW supplementation on in vitro gas production, ruminal digestion and fermentation characteristics. Materials & Methods: The experiment followed a completely randomized design with a 2×3 factorial arrangement of treatments with a control. The control treatment was total mixed ration (TMR) without any supplementation. Factor A was the type of GTW (containing fresh or dried GTW; FGTW and DGTW, respectively), and factor B was the level of GTW addition in TMR at rates of 5%, 10% or 15% on a dry matter (DM) basis. Results: There was no interaction between the type and level of GTW supplementation on in vitro gas production, gas kinetics and ruminal fermentation end products, except for the in vitro digestibility of nutrients. Compared with the control, the addition of GTW resulted in significantly higher levels of in vitro gas production, in vitro digestibility of DM and organic matter (IVDMD and IVOMD), and total volatile fatty acid (VFA). Furthermore, the DGTW supplementation showed higher levels of gas production, IVDMD, IVOMD, ruminal NH3-N and total VFA concentration compared with FGTW, particularly when 10–15% GTW was added. Main finding: GTW could be effectively used as ruminant feed and the addition of DGTW in the TMR could enhance gas production, ruminal digestion and fermentation end products. Further in vivo study is needed to evaluate the use of GTW on animal performance.